Profile of Condylomata Acuminata in Patients with HIV/AIDS - Dian Pertiwi Habibie; Jusuf Barakbah (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Condylomata acuminata is human papilloma virus (HPV) infection, and one of the most common sexually transmitted disease, characterized with papul or papillomatous nodul in genital, perineum and anal, this disease can be asymptomatic as well. Some study proved sexually transmitted infection increase the incidence of Human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS), and vice versa. Purpose: To evaluate the profile of condylomata acuminata in HIV/AIDS patients. Methods: Retrospective study of the incident of condylomata acuminata in HIV/AIDS patients using medical record within 4 years period from 2011 to 2014. Results: HIV/AIDS patients in outpatient clinic intermediate care infection disease unit RSUD Dr.Soetomo Surabaya in period 2011-2014 is 4057 patients, 63 (1.15%) of it with condylomata acuminata. HIV/AIDS patients with condylomata acuminata at the age group 25-44 (69.8%), the most sexual partner is heterosexual (58.7%), CD4+ count group mostly shown < 200/mm3 (46.0%), most of the patients got antiretroviral therapy (ART) as 66.7%, the most therapy for condylomata acuminata is trichloracetic acid (TCA) with fucidic acid (98.4%), most of the patient through 1-3 times therapy (50.8%), and the result is mostly not yet healed (76.2%). Conclusion: Most of condylomata acuminata patient in outpatient clinic intermediate care infection disease unit (UPIPI) got ART, TCA, and fucidic acid, and not complete resolution.